2006
DOI: 10.1136/ijgc-00009577-200605000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative radiation therapy improves prognosis in patients with adverse risk factors in localized, early-stage cervical cancer: a retrospective comparative study

Abstract: The objective of this study was to assess the role of postoperative radiotherapy (RT) in early-stage cervical carcinoma with risk factors other than positive nodes, parametrial invasion, or positive margins and to compare outcomes using the Leiden University Medical Center (LUMC) modification of the Gynecologic Oncology Group (GOG) system with the GOG prognostic scoring system itself. Between January 1984 and April 2005, 402 patients with early-stage cervical cancer underwent radical hysterectomy. A total of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…[12] However, the difference was not surprising because the group of Memarzadeh et al comprised of the general population of cervical cancer patients, whereas we only included subjects with at least one of the following risk factors confirmed during a histological examination: Depth of invasion of ≥15 mm, parametrial invasion and lymph nodes involvement. [1][2][3][4] A comparison of our incidence with that reported by Memarzadeh et al, in their study revealed that risk factors increase the incidence of parametrial PSI by over two-fold. In other studies, PSI was assessed in the cervix.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…[12] However, the difference was not surprising because the group of Memarzadeh et al comprised of the general population of cervical cancer patients, whereas we only included subjects with at least one of the following risk factors confirmed during a histological examination: Depth of invasion of ≥15 mm, parametrial invasion and lymph nodes involvement. [1][2][3][4] A comparison of our incidence with that reported by Memarzadeh et al, in their study revealed that risk factors increase the incidence of parametrial PSI by over two-fold. In other studies, PSI was assessed in the cervix.…”
Section: Discussionsupporting
confidence: 74%
“…[1][2][3] These factors may greatly influence the selection of patients for adjuvant therapy. [4] Perineural space invasion (PSI) qualifies for inclusion into the group of patients with poor prognostic factors. [5,6] PSI can be observed in the absence of vascular or lymphatic invasion and can be the sole route of metastatic spread.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately these studies were either small with only 17 patients in the surgery-only arm15 or showed a better recurrence-free survival without a difference in overall survival 16 17. One of the subjects that is not often considered in the studies discussed so far is the type or quality of surgery that was used.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the risk factors, the risk scoring criteria were settled through a modification of the previous criteria. 10 The final score for each patient was calculated by summing up her points, and the patient was assigned to the low-, intermediate-, or high-risk group ( Table 1). The best cutoff value for differentiating the low-risk group from the intermediate-/high-risk group was confirmed using the receiver operating characteristic (ROC) curve analysis.…”
Section: Methodsmentioning
confidence: 99%